A platform for customization and publication of open educational games - Beder, Delano M.; Otsuka, Joice L. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
In a complex and expensive area, such as the development of educational games, solutions that advocate collaboration, sharing, and reuse are important in order to make possible the area advance and also encourage that these educational resources can be effectively used by their target audience: teachers and students. This article presents the REMAR1 platform which aims to make easier the creation and sharing of open educational games. Besides, this article presents the initial results obtained in the pilot tests involving the proposed platform usage by students, teachers and game developers.